The Secular Landscape : The Decline of Religion in America - McCaffree, Kevin (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book proposes a comprehensive theory of the loss of religion in human societies, with a specific and substantive focus on the contemporary United States. Kevin McCaffree draws on a range of disciplines including sociology, psychology, anthropology, and history to explore topics such as the origin of religion, the role of religion in recent American history, the loss of religion, and how Americans are dealing with this loss. The book is not only richly theoretical but also empirical. Hundreds of scientific studies are cited, and new statistical analyses enhance its core arguments. What emerges is an integrative and illuminating theory of secularization.